The COVID-19 pandemic: new concerns and connections between eHealth and digital inequalities. Issue 3 (25th June 2020) - Khilnani, Aneka; Schulz, Jeremy; Robinson, Laura
Abstract : Purpose: Telemedicine has been advancing for decades and is more indispensable than ever in this unprecedented time of the COVID-19 pandemic. As shown, eHealth appears to be effective for routine management of chronic conditions that require extensive and repeated interactions with healthcare professionals, as well as the monitoring of symptoms and diagnostics. Yet much needs to be done to alleviate digital inequalities that stand in the way of making the benefits of eHealth accessible to all. The purpose of this paper is to explore the recent shift in healthcare delivery in response to the COVID-19 pandemic towards telemedicine in healthcare delivery and show how this rapid shift is leaving behind those without digital resources and exacerbating inequalities along many axes. Design/methodology/approach: Because the digitally disadvantaged are less likely to use eHealth services, they bear greater risks during the pandemic to meet ongoing medical care needs. This holds true for both medical conditions necessitating lifelong care and conditions of particular urgency such as pregnancy. For this reason, the authors examine two case studies that exemplify the implications of differential access to eHealth: the case of chronic care diseases such as diabetes requiring ongoing care and the case of time-sensitive health conditions such as pregnancy that may be compromised by gaps in continuous care. Findings: Not only are the digitally disadvantaged more likely to belong to populations experiencing greater risk – including age and economic class – but they are less likely to use eHealth services and thereby bear greater risks during the pandemic to meet ongoing medical care needs during the pandemic. Social implications: At the time of writing, almost 20% of Americans have been unable to obtain medical prescriptions or needed medical care unrelated to the virus. In light of the potential of telemedicine, this does not need to be the case. These social inequalities take on particular significance in light of the COVID-19 pandemic. Originality/value: In light of the COVID-19 virus, ongoing medical care requires exposure to risks that can be successfully managed by digital communications and eHealth advances. However, the benefits of eHealth are far less likely to accrue to the digitally disadvantaged.